Pdx-1-Driven Overexpression of Aurora A Kinase Induces Mild Ductal Dyplasia of Pancreatic Ducts Near Islets in Transgenic Mice - Warner, Steven L. (2008)
OBJECTIVES: To further explore the oncogenic activity of Aurora A kinase while attempting to develop a useful mouse model for pancreatic cancer, Aurora A kinase was targeted to Pdx-1 positive cells. METHODS: Aurora A kinase overexpression was targeted to mouse pancreas tissue using the Pdx-1 promoter in a transgenic model. The pancreas tissue of 7–11 month old transgenic animals were evaluated for metastatic adenocarcinomas, preinvasive ductal neoplasia, or other histological anomalies. RESULTS: Examination of pancreatic tissue from Pdx-1-Aurora A transgenic mice revealed abnormalities, such as mild islet cell hyperplasia, lymphocytic infiltration, and general dysplasia between ductal/islet cell interfaces. However, the majority of the tissue from these transgenic mice was normal. CONCLUSIONS: The overexpression of Aurora A can potentially initiate the development of mild abnormalities in pancreatic tissue; however, neither preinvasive ductal neoplasia nor fully metastatic adenocarcinomas were observed. Combining the Pdx-1-Aurora A transgenic model with other genetic alterations may provide additional insight.